2007
DOI: 10.1345/aph.1k187
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Infection with Intravenous Iron Therapy

Abstract: Despite the limited human data, careful consideration of risk versus benefit should be used when administering intravenous iron to patients with ongoing infection. Additional clinical data are needed to determine whether intravenous iron administration worsens outcomes of patients with infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Although some recommend withholding iron during acute infection, [25][26][27][28] others argue that the evidence supporting this recommendation is weak. 21,29 We also observed an association between dosing practices and risk of infection-related mortality. The existing epidemiologic evidence linking iron exposure and mortality is inconclusive, with some studies finding evidence of harm, 30,31 one study finding no association, 32 and one study finding benefits in patients with severe anemia but risks in patients with mild anemia.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although some recommend withholding iron during acute infection, [25][26][27][28] others argue that the evidence supporting this recommendation is weak. 21,29 We also observed an association between dosing practices and risk of infection-related mortality. The existing epidemiologic evidence linking iron exposure and mortality is inconclusive, with some studies finding evidence of harm, 30,31 one study finding no association, 32 and one study finding benefits in patients with severe anemia but risks in patients with mild anemia.…”
Section: Discussionmentioning
confidence: 54%
“…[11][12][13][14][15] Although the role of iron in bacterial growth and infection risk is biologically plausible and has been shown in animal models, 12,[20][21][22] data from large CKD populations on iron and infections are lacking. An abstract reported that frequency of iron administration was associated with increased risk of infection-related mortality in ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the practice of administering IV iron to patients with systemic infection is generally avoided in clinical practice, in large part on the basis of animal studies showing worsening of systemic infections in subjects treated with IV iron [7880]. …”
Section: Does IV Iron Increase the Risk Of Infection?mentioning
confidence: 99%
“…In this case, DCI level was 18.59 μM and such a high concentration of this NTBI fraction could be caused by intrauterine infection of the newborn. It has been shown that iron is significant in bacterial metabolism and can promote infection .…”
Section: Resultsmentioning
confidence: 99%